(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2019)
This article aims to show the validity of an actualization of William James’s pragmatist epistemology of psychology for the construction of personal identity. Following Giovanni Maddalena’s theoretical hypothesis of “gesture” as a complete synthetic tool for the acquisition of knowledge, an in-depth analysis of the continuous and dynamic conception of personal identity proposed by James may be helpful today to better develop the emotional-somatic dimension of synthetic reasoning. As far as the epistemology of the Self is concerned, significant continuities and discontinuities are drawn from James’s naturalized integrated conception of personal identity in the light of this new Peirce’s inspired interpretation. This attempt is part of a wider project in which recovering the character of psychological and ontological processual continuity in James’s epistemology makes a considerable contribution to the development of a comprehensive understanding of mental models, one that avoids to tighten up these models as it happens in most of the contemporary epistemologies of the self.